Study of the Distribution and Physico-Chemical Properties of Deep Groundwater in Some Areas of the Altiaryk and Besharik Districts of the Fergana Region and Their Rational Use (Eurasian Journal of Engineering and Technology, 2022)
This article deals with the distribution of deep groundwater, their physicochemical properties, practical significance, methods for determining the composition of deep groundwater brought from different regions of the region, as well as methods of water hardness and hard water softening, solid minerals (Ca and Mg elements) data on the negative effects of rich waters on plants and their prevention.